Is It Time to Start Transitioning From 2D to 3D Cell Culture? - Jensen, Caleb; Teng, Yong (Frontiers in Molecular Biosciences, 2020)
Cell culture is an important and necessary process in drug discovery, cancer research, as well as stem cell research. Most cells are currently cultured using two-dimensional (2D) methods, but new and improved methods that implement three-dimensional (3D) cell culture techniques suggest compelling evidence that much more advanced experiments can be performed. When performing 3D cell culture experiments, the cell environment can be manipulated to mimic that of a cell in vivo and provide more accurate data about cell-to-cell interactions, tumor characteristics, drug discovery, metabolic profiling, stem cell research, and other types of diseases. Scaffold based techniques such as hydrogel-based support, polymeric hard material-based support, hydrophilic glass fiber, and organoids are employed, and each provides its own advantages and applications. Likewise, there are also scaffold-free techniques used such as hanging drop microplates, magnetic levitation, and spheroid microplates with ultra-low attachment coating. 3D cell culture has the potential to provide alternative ways to study organ behavior via the use of organoids and is expected to eventually bridge the gap between 2D cell culture and animal models. The present review compares 2D cell culture to 3D cell culture, provides the details surrounding the different 3D culture techniques, as well as focuses on the present and future applications of 3D cell culture.